Theoretical and experimental study for the biomimetic recognition of levothyroxine hormone on magnetic molecularly imprinted polymer - Moura, Silio Lima; Fajardo, Laura Martinez; Cunha, Leonardo dos Anjos; Sotomayor, Maria Del Pilar Taboada [UNESP]; Machado, Francisco Bolivar Correto; Ferrão, Luiz Fernando Araújo; Pividori, Maria Isabel (Elsevier, 2018)
This study addresses the rational design of a magnetic molecularly imprinted polymer (magnetic-MIP) for the selective recognition of the hormone levothyroxine. The theoretical study was carried out by the density functional theory (DFT) computations considering dispersion interaction energies, and using the D2 Grimme's correction. The B97-D/def2-SV(P)/PCM method is used not only for studying the structure of the template the and monomer-monomer interactions, but also to assess the stoichiometry, noncovalent binding energies, solvation effects and thermodynamics properties such as binding energy. Among the 13 monomers studied in silico, itaconic acid is the most suitable according to the thermodynamic values. In order to assess the efficiency of the computational study, three different magnetic-MIPs based on itaconic acid, acrylic acid and acrylamide were synthesized and experimentally compared. The theoretical results are in agreement with experimental binding studies based on laser confocal microscopy, magneto-actuated immunoassay and electrochemical sensing. Furthermore, and for the first time, the direct electrochemical sensing of L-thyroxine preconcentrated on magnetic-MIP was successfully performed on magneto-actuated electrodes within 30 min with a limit of detection of as low as 0.0356 ng mL−1 which cover the clinical range of total L-thyroxine. Finally, the main analytical features were compared with the gold standard method based on commercial competitive immunoassays. This work provides a thoughtful strategy for magnetic molecularly imprinted polymer design, synthesis and application, opening new perspectives in the integration of these materials in magneto-actuated approaches for replacing specific antibodies in biosensors and microfluidic devices.
Keywords: Electrochemical sensing; L-thyroxine; Magnetic actuation; Magnetic-MIP; Rational MIP design